Frequency and characteristics of diabetes in lipodystrophies and insulin receptoropathies compared with type 1 and type 2: results from the multicenter DPV registry - Kamrath, Clemens; Eckert, Alexander; Rami-Merhar, Birgit; Kummer, Sebastian; Wabitsch, Martin; Laubner, Katharina; Kopp, Florian; Müther, Silvia; Mühldorfer, Steffen; Holl, Reinhard W. (Endocrine Connections, 2023)
Objective: To investigate the frequency, treatment, and outcome of patients with diabetes due to severe insulin resistance syndromes (SIRS). Research Design and Methods: Based on data from the multicenter prospective Diabetes Registry DPV, we analyzed diagnosis, treatment, and outcome of 636,777 patients with diabetes from 1995 to 2022. Results: Diabetes due to SIRS was documented in 67 cases (62.7% females), 25 (37%) had lipodystrophies (LD) and 42 (63%) had congenital defects of insulin signaling. The relative frequency compared to type 1 diabetes (T1D) was about 1:2300. Median age at diabetes diagnosis in patients with SIRS was 14.8 years (interquartile range (IQR) 12.8–33.8). A total of 38 patients with SIRS (57%) received insulin and 34 (51%) other antidiabetics, mostly metformin. As high as 16% of patients with LD were treated with fibrates. Three out of eight patients with generalized LD (37.5%) were treated with metreleptin and one patient with Rabson–Mendenhall syndrome was treated with recombinant insulin-like growth factor 1. The median glycated hemoglobin level at follow-up was 7.1% (54 mmol/mol). Patients with LD had higher triglycerides than patients with T1D and T2D (P < 0.001 and P = 0.022, respectively), and also significantly higher liver enzymes and lower high-density lipoprotein cholesterol than patients with T1D (P < 0.001). Patients with insulin receptor disorders were significantly less likely to be treated with antihypertensive medication than patients with T2D (P = 0.042), despite having similar levels of hypertension. Conclusions: Diabetes due to SIRS is rarely diagnosed and should be suspected in lean children or young adults without classical T1D. Awareness of cardiovascular risk factors in these patients should be raised.
CRIS-Team Scopus Importer:2023-03-10
Keywords: diabetes; rare diseases/syndromes